2022
DOI: 10.1186/s12943-022-01672-z
|View full text |Cite
|
Sign up to set email alerts
|

NK cells and solid tumors: therapeutic potential and persisting obstacles

Abstract: Natural killer (NK) cells, which are innate lymphocytes endowed with potent cytotoxic activity, have recently attracted attention as potential anticancer therapeutics. While NK cells mediate encouraging responses in patients with leukemia, the therapeutic effects of NK cell infusion in patients with solid tumors are limited. Preclinical and clinical data suggest that the efficacy of NK cell infusion against solid malignancies is hampered by several factors including inadequate tumor infiltration and persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 245 publications
(302 reference statements)
1
51
0
Order By: Relevance
“…To further verify these associations, we adopted another algorithm, CIBERSORT, to assess the abundance of 22 immune components. In most cancers, CAFs had a negative correlation with CD8+ T cells and activated NK cells, both of which are well‐known for their anti‐tumor functions 65,66 . Conversely, M0 and M2 macrophages showed positive correlation with CAFs in most cancers (Figure 2E).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To further verify these associations, we adopted another algorithm, CIBERSORT, to assess the abundance of 22 immune components. In most cancers, CAFs had a negative correlation with CD8+ T cells and activated NK cells, both of which are well‐known for their anti‐tumor functions 65,66 . Conversely, M0 and M2 macrophages showed positive correlation with CAFs in most cancers (Figure 2E).…”
Section: Resultsmentioning
confidence: 92%
“…In most cancers, CAFs had a negative correlation with CD8+ T cells and activated NK cells, both of which are wellknown for their anti-tumor functions. 65,66 Conversely, M0 and M2 macrophages showed positive correlation with CAFs in most cancers (Figure 2E). These results indicated that CAFs could recruit tumor-promoting immune cells, while excluding anti-tumor cells, further remodelling the TME and promoting tumor progression.…”
Section: Clinical Relevance Of Cafs and Their Correlation With Other ...mentioning
confidence: 92%
“…After consulting the literature, we learned that whether the function of NK cells can work is closely related to cell metabolism functions, such as cell hypoxia, energy supply, amino acid cycle, etc [33,34] . FasL-related GTP-related signal pathway is also involved [35] . The results and enrichment results corroborated with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the induction of a memory-like phenotype using IL-2, IL-15, and IL-18 holds great potential in improving both the cytotoxicity and persistence of NK cells [69]. To date, the most prominent success in NK cell adoptive transfer has been with IL-15-enhanced CAR-NK products against CD19-expressing lymphomas, while progress in other hematologic malignancies and solid tumor targets remain in earlier investigational stages [6,181,185]. Nonetheless, the recent advances in NK cell therapies and other methods in leveraging NK cell cytotoxicity have demonstrated the great promise of this cellular therapy platform.…”
Section: Discussionmentioning
confidence: 99%